2002
DOI: 10.1097/00007632-200206010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Four Conservative Treatments for Subacute Low Back Pain

Abstract: For subacute low back pain, combined joint manipulation and myofascial therapy was as effective as joint manipulation or myofascial therapy alone. Additionally, back school was as effective as three manual treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 21 publications
3
71
0
3
Order By: Relevance
“…The 6 case studies were given a ranking of 4 in the CEBM scale (Table 2) and received no score on the PEDro scale (Table 1). Ethical approval was confirmed in only 5 studies (Enebo, 6 Hanten and Chandler, 7 Hseih et al, 8 Kuhar et al, 9 and LeBauer et al 10 ); 1 study 8 reported participant incentives of money or free chiropractic treatments (or both). Only 1 of the 6 case studies reported that participants gave informed consent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 6 case studies were given a ranking of 4 in the CEBM scale (Table 2) and received no score on the PEDro scale (Table 1). Ethical approval was confirmed in only 5 studies (Enebo, 6 Hanten and Chandler, 7 Hseih et al, 8 Kuhar et al, 9 and LeBauer et al 10 ); 1 study 8 reported participant incentives of money or free chiropractic treatments (or both). Only 1 of the 6 case studies reported that participants gave informed consent.…”
Section: Resultsmentioning
confidence: 99%
“…Hsieh et al 8 conducted a high-quality study, ranked at level 1b on the Levels of Evidence scale and earning 7 of 10 points on the PEDro scale. The 1b rating reflects a study that was well designed, with a sufficient number of participants and adequate long-term follow-up.…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, therapists are often selected to participate in clinical research studies based on having more years of clinical experience or greater experience with manual physical therapy, without any further attempt to insure that the chosen therapists actually achieve better outcomes when caring for patients. 1,20,22,36,38 This is done based on the assumption that increased years of experience marks an expert therapist, and that these individuals will, consequently, deliver superior patient care. Our results did not support this premise.…”
Section: Discussionmentioning
confidence: 99%
“…5,11,17 The presumed importance of experience with manipulative interventions is evidenced by studies of manipulation that require a certain level of experience for the practitioners administering the manipulation interventions. 1,20,22,36 Exercise interventions, including spinal stabilization programs, have also been shown to improve clinical outcomes in patients with LBP. 21,38 The expertise of the therapist has been suggested to play an important role in the success with stabilization exercise interventions, 37 although it does not appear that as much attention has been focused on therapist-related factors and their influence on the outcomes of exercise interventions.…”
mentioning
confidence: 99%